Role of Proteolysis in Determining Potency of Bacillus thuringiensis Cry1Ac δ-Endotoxin - Lightwood, Daniel J. (American Society for Microbiology, 2000)
Bacillus thuringiensis protein δ-endotoxins are toxic to a variety of different insect species. Larvicidal potency depends on the completion of a number of steps in the mode of action of the toxin. Here, we investigated the role of proteolytic processing in determining the potency of the B. thuringiensis Cry1Ac δ-endotoxin towards Pieris brassicae (family: Pieridae) and Mamestra brassicae (family: Noctuidae). In bioassays, Cry1Ac was over 2,000 times more active against P. brassicae than against M. brassicae larvae. Using gut juice purified from both insects, we processed Cry1Ac to soluble forms that had the same N terminus and the same apparent molecular weight. However, extended proteolysis of Cry1Ac in vitro with proteases from both insects resulted in the formation of an insoluble aggregate. With proteases from P. brassicae, the Cry1Ac-susceptible insect, Cry1Ac was processed to an insoluble product with a molecular mass of ∼56 kDa, whereas proteases from M. brassicae, the non-susceptible insect, generated products with molecular masses of ∼58, ∼40, and ∼20 kDa. N-terminal sequencing of the insoluble products revealed that both insects cleaved Cry1Ac within domain I, but M. brassicae proteases also cleaved the toxin at Arg423 in domain II. A similar pattern of processing was observed in vivo. When Arg423 was replaced with Gln or Ser, the resulting mutant toxins resisted degradation by M. brassicae proteases. However, this mutation had little effect on toxicity to M. brassicae. Differential processing of membrane-bound Cry1Ac was also observed in qualitative binding experiments performed with brush border membrane vesicles from the two insects and in midguts isolated from toxin-treated insects.